La maschera e la morte. Sulla categoria di impersonale, da una prospettiva storico-culturale - Lucci, Antonio (Philosophy Kitchen - Rivista di filosofia contemporanea, 2016)
This contribution proposes an analysis of the “person” category starting from the anthropological theories conceived by three authors:Thomas Macho, Marcel Mauss and Karl Meuli. By means of a detailed study of some of their paradigmatic texts, an autonomous interpretation of the concept of “impersonal” will be presented, connecting its meaning to the idea of death intended from a culturological perspective. Conceived as the background of past generations determining the position of the unborn child in the society he or she belongs to, death becomes the “impersonal” at the core of the whole essay.